Late Quaternary benthic foraminifera from Ocean Drilling Program Hole 716A, Maldives Ridge, southeastern Arabian Sea - Sarkar, S.; De, S.; Gupta, A. K. (Micropaleontology, 2009)
A study on deep-sea benthic foraminifera from the interval similar to 445 ka BP to the Present of the Ocean Drilling Program (ODP) Hole 716A (4 degrees 56.0'N, 73 degrees 17.0'E; preser t water depth 533.3m), Maldives Ridge. southeastern Arabian Sea, documented 201 species belonging to 105 genera. These taxa were examined under scanning electron microscope (SEM) to illustrate their interspecific morphological variations. Several of these species are dominant showing significant down core fluctuations in their abundances whereas some are rare and sporadic.
424cdTimes Cited:5 Cited References Count:47
Keywords: benthonic foraminifera; equatorial indian-ocean; Holocene; late neogene; monsoon; Oxygen minimum zone; productivity; red-sea; south atlantic-ocean; Water masses